2015
DOI: 10.1177/1535370214560965
|View full text |Cite
|
Sign up to set email alerts
|

Atoh7 promotes the differentiation of Müller cells-derived retinal stem cells into retinal ganglion cells in a rat model of glaucoma

Abstract: Glaucoma is one of the leading eye diseases resulting in blindness due to the death of retinal ganglion cells. This study aimed to develop novel protocol to promote the differentiation of retinal Mü ller cells into ganglion cells in vivo in a rat model of glaucoma. The stem cells dedifferentiated from rat retinal Mü ller cells were randomized to receive transfection with empty lentivirus PGC-FU-GFP or lentivirus PGC-FU-Atoh7-GFP, or no transfection. The stem cells were induced further to differentiate. Ocular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…Glaucoma is an eye disease characterized by optic atrophy and visual field loss and has become a major disease that affects/ human life, which could result in blindness because of the death of RGCs [23, 24]. Presently, although surgery or drugs are often used to control IOP, patients with controlled IOP still suffer from optic atrophy and RGC apoptosis [25, 26].…”
Section: Discussionmentioning
confidence: 99%
“…Glaucoma is an eye disease characterized by optic atrophy and visual field loss and has become a major disease that affects/ human life, which could result in blindness because of the death of RGCs [23, 24]. Presently, although surgery or drugs are often used to control IOP, patients with controlled IOP still suffer from optic atrophy and RGC apoptosis [25, 26].…”
Section: Discussionmentioning
confidence: 99%
“…Müller cells can obtain retinal stem cell characteristics under specific conditions . Retinal Müller cells cultured in serum‐free medium supplemented with N2 and B27 could dedifferentiate into retinal stem cells and express stem cells marker Nestin and proliferation marker Ki‐67 .…”
Section: Discussionmentioning
confidence: 99%
“…The scotopic aand b-waves were significantly higher in MNU model rats receiving subretinal injection of lentivirus pGC-FU-Otx2-EGFP infected MC-RSCs than in MNU model rats or MNU model rats receiving subretinal injection of lentivirus pGC-FU-EGFP infected MC-RSCs (Figure 7A,B). These results suggest that photoreceptor function has better recovery after transplantation of MC-RSCs with Otx2 overexpression.4 | DISCUSSIONMüller cells can obtain retinal stem cell characteristics under specific conditions 11,23. Retinal Müller cells cultured in serum-free medium supplemented with N2 and B27 could dedifferentiate into retinal stem cells and express stem cells marker Nestin and proliferation marker Ki-67 21.…”
mentioning
confidence: 89%
“…The enrichment of Müller cells and differentiation into RGCs were performed as previously described [7].…”
Section: Dedifferentiation Of Purified Müller Cells Into Retinal Stemmentioning
confidence: 99%
“…The dedifferentiated retinal Müller cells then differentiate into different types of neurons such as retinal ganglion cells (RGCs). Our previous studies showed that RGCs derived from Müller cells had defects in axon growth, leading to a defect in signal conduction [6,7].…”
Section: Introductionmentioning
confidence: 99%